Community health workers improving diabetes outcomes in a rural Appalachian population. (7th February 2017) - Feltner, Frances; Thompson, Sydney; Baker, William; Slone, Melissa
ABSTRACT: Community health workers (CHWs) play a key role in the emerging health infrastructure. They are successful in identifying individual or family needs and matching resources to help overcome the social determinants of health, and the lack of trust in the health care system. This study captures the CHW experience as research assistants and evaluates the effectiveness of CHWs' health coaching and support in improving diabetes health outcomes. By being immersed in the culture and values of the population, CHWs offer research support to assure more representative client samples, increased adherence to study protocols, and in reducing attrition rates.